No future without forgiveness - Tutu, Desmond (1999)
"The establishment of South Africa's Truth and Reconciliation Commission was a pioneering international event. At the center of this attempt at healing a nation has been Archbishop Desmond Tutu, whom President Nelson Mandela named as Chairman of the Truth and Reconciliation Commission. With the final report of the Commission just published, Archbishop Tutu offers his reflections on South Africa." "In No Future Without Forgiveness, Tutu argues that true reconciliations cannot be achieved by denying the past. But nor is it easy to reconcile when a nation "looks the beast in the eye." Rather than repeat platitudes about forgiveness, he presents a spirituality that recognizes the horrors people can inflict upon one another, and yet retains a sense of idealism about reconciliation."--Jacket
The Prelude -- Nuremberg or National Amnesia? A Third Way -- In the Fullness of Time -- What About Justice? -- Up and Running -- A Victim Hearing -- "We do Want to Forgive, But We Don't Know Whom To Forgive" -- "This is My Brother. I Know Those Shoes." -- Why the Heck Am I Doing This Thankless Job? -- "We Did not Know" -- Without Forgiveness There Really is no Future
Includes bibliographical references
Keywords: South Africa. -- Truth and Reconciliation Commission; Forgiveness -- Religious aspects -- Christianity; Reconciliation -- Religious aspects -- Christianity; South Africa -- Race relations; Truth and Reconciliation Commission